Establishment and analysis of in vitro biomass from Salvia corrugata Vahl. and evaluation of antimicrobial activity. (February 2016) - Bisio, Angela; Fraternale, Daniele; Schito, Anna Maria; Parricchi, Anita; Dal Piaz, Fabrizio; Ricci, Donata; Giacomini, Mauro; Ruffoni, Barbara; De Tommasi, Nunziatina
Graphical abstract: In vitro biomass of S. corrugata was evaluated for the production of the main icetexane constituents and of other diterpenes, and for the antimicrobial activity of its extracts. Highlights: Demethylfruticuline A and fruticuline A are the main constituents of S. corrugata . Protocols for callus culture, micropropagation, shoot regeneration were established. The content of demethylfruticuline A and fruticuline A was determined. The in vitro plant material afforded also one icetexane and six abietane diterpenes. The antimicrobial activity of the extracts and of two compounds was evaluated. Abstract: Demethylfruticuline A and fruticuline A, the most abundant compounds from the surface extract of Salvia corrugata Vahl., have shown antibacterial, antitumor and cytotoxic activities. In order to obtain these icetexane diterpenes from in vitro cultures of S. corrugata, protocols were developed for callus production, micropropagation and shoot regeneration. Analysis of the regenerated shoots showed the presence of both icetexanes, micropropagated plants contained only fruticuline A, while the callus contained trace amounts of both diterpenes. The yield of fruticuline A was higher in the methanolic extract of regenerated shoots than in those of fresh leaves and fresh shoot tips. In addition to these diterpenes, the regenerated shoot and micropropagated plant extracts afforded seven other diterpenes, one icetexane and six abietanes, identified by UV, IR, 1D- and 2D-NMR and HR-MS analysis. Five compounds (19-acetoxy-7α-hydroxyroyleanone, 7β, 20-epoxy-11, 12, 19-trihydroxyabieta-8, 11, 13-triene, 7, 20-dihydrofruticuline A, 7β-acetoxy-20-hydroxy-19, 20-epoxyroyleanone, 7β-ethoxy-6β, 20:19, 20-diepoxyroyleanone) were previously undescribed. Although the crude plant surface extract did not possess any antibacterial activity, methanolic extracts of in vitro tissues and two compounds, namely 7β-acetoxy-20-hydroxy-19, 20-epoxyroyleanone and 7β-ethoxy-6β, 20:19, 20-diepoxyroyleanone, isolated in suitable amounts, were active in varying degrees against multidrug resistant clinical strains of Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis and Enterococcus faecium, displaying MIC values ranging from 32, 64 to 128 μg/mL.